Revisiting perceived determinants of tourism destination competitiveness among tourists : The case of national parks in Sarawak, Malaysia - Thong, Jun Zhou; Lo, May Chiun; Thurasamy, Ramayah; Abang Azlan, Mohamad (Lodz University Press, 2022)
The present study aims to widen the existing literature by discovering potential determining factors at selected ecotourism destinations, primarily involving Bako, Niah, Kubah, Gunung Gading and Gunung Mulu National Parks. A closed questionnaire was answered by 188 respondents. Preliminary analyses were performed and partial least square structural equation modeling was employed as the analytical measure, thus discovering the significant role of destination resource constructs in the enhancement of ecotourism competitiveness in Sarawak, Malaysia. The statistical findings of the current work revealed that endowed resources (natural resources and cultural heritage attractions), created resources (range of activities) as well as supporting resources (destination accessibility and quality of tourism services) lead to enhanced tourism destination competitiveness. The research adds to the growing body of knowledge examining the perspectives of tourists towards the determining factors of destination competitiveness, while providing meaningful insights for industry actors, thus enabling effective planning of management and development. The present work offers empirical evidence that gives information for industry stakeholders, including business operators, poli